A SUPERAÇÃO DE CONFLITOS PRODUZIDOS PELA ANSIEDADE: UMA CONTRIBUIÇÃO À PRÁXIS PASTORAL, A PARTIR DA TEORIA DA INTERPESSOALIDADE - Marinho, Marco Lécio Mendes (2008)
The object of this research is to clarify how the anxiety plays a major role influencing the interpersonal relations and how this knowledge, followed by a conscious attitude that allows the minimization of the anxiety would give place to harmonic relationships and the decrease of the every day life conflicts. Based on a bibliographic review, authors of correlated areas as psychology, counseling, philosophy and theology were consulted, for the acknowledgement that exist a huge volume of Scientific information about the theme that might add positively to this study. A dialectic that considers the genesis, of the social relations and of the influences that build interpersonal and intrapersonal individual behavior is exploited as well as the emotional non satisfaction produced by anxiety. The contribution of this research is related to the viability of conquering more healthy relationships; the development of the idea of a conscious action, an attitude less influenced by anxiety; and the highlighting of the importance of pastoral practice based on faith as the hope that minimizes the anxiety element. Its value points to a hope on harmonic interpersonal relations, not a utopian one, but one that is product of knowledge, discernment and comprehension of the individual intra and interpersonal reality.(AU)